Subsidy or policy certainty: Which attribute is more important for broiler farmers when investing in particulate matter abatement technology?. (15th September 2022) - Vissers, Luuk S.M.; Sok, Jaap; Oude Lansink, Alfons G.J.M.
Abstract: Broiler houses are an important source of particulate matter (PM) in the Netherlands. High concentrations of PM can threaten the environment and pose health risks to humans and animals. To address these problems, the Dutch government aims to reduce PM10 emissions originating from broiler houses by 50% between 2020 and 2030. This paper explored broiler farmers' investment preferences for different PM10 abatement techniques and how they relate to socio-economic characteristics and perceived obstacles for business development. The results of our discrete choice experiment indicate that farmers were reluctant to invest in PM10 abatement techniques. When they did invest, they had a general preference for techniques with a medium to high (31–52%) rather than a very high PM10 reduction efficiency (80%). Social factors and perceived obstacles for business development explained heterogeneity in farmers' preferences for PM10 abatement techniques and their willingness to invest. When investing in abatement techniques, farmers attached a higher relative importance to an exemption from future PM10 legislation than to a subsidy. The findings imply that more policy-related certainty as well as financial compensation can incentivize farmers to invest in PM10 abatement. Graphical abstract: Image 1 Highlights: Preferences for particulate matter abatement technique attributes were quantified. Dutch broiler farmers were reluctant to invest in these techniques. When they did invest, they preferred techniques with a medium reduction efficiency. They attached a higher relative importance to policy certainty than to a subsidy. Social factors and perceived obstacles explained heterogeneity in preferences.